Utilization and surveillance of Fisheries Tuna Resources as a Basis for Prevention of IUU Fishing in Seram Sea - Radjak, Syarif Abdul; Tupamahu, Agustinus; Tuapetel, Friesland; Haruna, Haruna; H.S Tawari, Ruslan (Agrikan Jurnal Agribisnis Perikanan, 2021)
This study aims to determine the conditions of tuna utilization, and to analyze the monitoring of tuna fisheries resources in preventing IUU fishing in Seram Sea Waters. Methods This research uses descriptive methods including primary and secondary data. Primary data comes from tuna fishermen respondents, fisheries monitoring agencies using purposive sampling and in-depth interviews, secondary data through literature studies. The results showed that the average tuna production in West Seram Regency was 4.10%, yellowfin tuna was 0.20%, the average CPUE of handline tuna fishermen was 505.86 kg/month/unit. The institutional capacity of fisheries supervisors needs to be improved, even though the vessel compliance indicator reaches 136%. Fishery violations during 2016-2018 are: violations of fishing routes and areas, violations of VMS, violations of fishing permits, and prohibitions on fishing by foreign people or vessels.